FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PEMBELIAN SMARTPHONE SAMSUNG SECARA ONLINE - SILVYA, MEGA; GULO, YUPITER (E-Jurnal Manajemen Trisakti School of Management (TSM), 2024)
This research aims to find out and analyze whether there is an influence of price, quality, security and trust on interest in purchasing Samsung smartphones online in DKI Jakarta. The sample in this study was 202 respondents. The form of research used in this research is descriptive and causality research. This research uses a purposive sampling technique. The data collection method was carried out by distributing questionnaires using a Likert scale. The analysis technique used is multiple linear regression analysis. Data processing from questionnaire results uses statistical data processing tools. Based on the results of hypothesis testing data analysis in this study, it shows that price, quality, security and trust influence interest in purchasing Samsung smartphones online in DKI Jakarta.